Vuelo a Shangri La - Diez, Eduardo; Pombo, Jorge and Moreno, Andres (Spain, 2011)
'Flight to Shangri-La' revisits the youth and history of a group of elderly people who gather amongst model planes and old photographs; they remain to be the last remaining aviators of the Spanish Republic.
Verzio Film Festival Submission
Keywords: Documentary films